A sense of belonging - James, Erica (Orion Books, 1998)
Cholmford Hall Mews, a converted eighteenth-century barn, offers more than an exclusive location in which to live. In their different ways, all the newcomers to Cholmford Hall Mews are searching for something -- love, peace of mind, a sense of belonging -- but will they find rather more than they bargained for?